Association of corn processing methods and sodium lasalocid for beef cattle on pasture during the finishing phase - Gonçalves, Paloma Helena; David, Gabriel Santos Souza [UNESP]; Prados, Laura Franco; Domingos, Bianca Rodrigues [UNESP]; Vellini, Beatriz Lima; Nascimento, Felipe Almeida; Foresto, Willian Manoel Ricardo; Silva, Naiara Caixeta da; Resende, Flávio Dutra de [UNESP]; Siqueira, Gustavo Rezende [UNESP] (Springer Nature, 2025)
We aimed to investigate the effects of corn processing methods and lasalocid in grazing cattle receiving high levels of concentrate on ruminal parameters, performance, and meat quality. Twelve cannulated animals were utilized to assess ruminal metabolism and sixty-four Nellore cattle to evaluate performance and meat quality. Four treatments were evaluated in a factorial scheme: dry corn (DC) without lasalocid; DC with lasalocid; high-moisture corn (HMC) without lasalocid, and HMC with lasalocid. Feeding HMC increased the ruminal proportion of propionate (P < 0.001). There was a trend (P = 0.08) toward increased ruminal acetate with lasalocid. There was an interaction observed between collection time and corn processing for acetate (P = 0.001) and propionate (P < 0.001). An interaction between corn processing, lasalocid, and collection time was detected for rumen pH (P = 0.03), while for rumen ammonia nitrogen, there was an trend of interaction between corn processing and time (P = 0.08). Regarding performance, HMC increased gain-to-feed ratio (P < 0.001) and average gain daily (P = 0.01) compared to DC, while decreasing concentrate intake (P = 0.01). An trend of interaction between lasalocid and corn processing was observed for carcass weight (P = 0.08), where the additive improved carcass performance in diets based on ensiled corn. There was a trend toward reduced ruminal content (P = 0.06) with grain ensilage and a trend toward increased rumen weight (P = 0.08). HMC increased the ether extract of the meat (P = 0.024). Feeding cattle on pastures with HMC enhances performance and reduces intake. Lasalocid improved carcass gain and pH of HMC-fed animals.